Intra-industry trade, endogenous technological change, wage inequality and welfare - Roberto A. De Santis (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
By using two alternative intra-industry trade models (1. - New goods cannot be introduced into the economy; 2. - The possibility for a set of capital goods available in the economy to vary; both models consider the existence of an intersectoral linkage), I show by means of Applied General Equilibrium (AGE) analysis that globalisation (either lower transport costs or lower tariffs) has an impact on the ratio between the wage rates of skilled and unskilled labours; but the impact on wage inequality is far larger, when countries are assumed to exchange differentiated capital goods. The latter result has been obtained by using an imperfect competitive model, which embodies a sector bias technological change that arises from trade. In addition, the gains from trade, insignificant under the standard trade hypotheses, are extraordinarily large when endogenous technological change is taken into account. The main policy conclusion is that if policy makers of flexible wage economies introduce trade barriers to reduce wage inequality, these protective measures, by affecting the diffusion of technology, would cause a large welfare loss.
Keywords: D58; F12; F43; J3; O3; 330; Trade; Technical change; Wage Inequality; Applied General Equilibrium; Intraindustrieller Handel; Neue Außenhandelstheorie; Allgemeines Gleichgewicht; Lohnstruktur; Endogener technischer Fortschritt; Humankapital; Globalisierung; Exportinduziertes Wachstum; Wohlfahrtseffekt; Theorie; Welt